Inhibition of Growth of Some Food Borne Bacteria by Falcaria vulgaris Extract - Ozturk, Suzan; Ozturk, Avni (Asian Journal of Chemistry, 2010)
Aerial parts of Falcaria vulgaris were successively extracted with methanol using a Soxhlet extractor, then the crude extract was screened for antibacterial activities. Extracts of Falcaria vulgaris were tested for their antibacterial activity in agar disk diffusion assays, whereas the minimum inhibitory concentrations (MIC) of single compounds were determined by the microbroth dilution method. Significant antibacterial activities were found against various strains, in particular Acidovorax facilis, Bacillus cereus, Bacillus dipsauri. Bacillus lentimorbus, Bacillus spp., Bacillus subtilis, Brevibacillus agri, Brevibacillus brevis, Corynebacterium ammoniagenes, Flavimonas oryzihabitans, Kocuria kristinae, Kocuria rosea, Micrococcus lylae. Paenibacillus apiarius, Paenibacillus macerans and Pseudomonas syringae syringae. These results support the ethnomedicinal use of Falcaria vulgaris both for treatment of infectious diseases and use as preservative in traditional herby cheese. This result may also suggest that the methanol extracts of Falcaria vulgaris possess compounds with antibacterial properties and thus can be used as a natural preservative ingredient in food and pharmaceutical industry.